Zinner’s Syndrome: Case Report of a Rare Maldevelopment in the Male Genitourinary Tract - Célia Sousa; Inês Portugal Teixeira; Sofia Helena Ferreira; Ana Teixeira; Sílvia Costa Dias (Journal of Urological Surgery)

(untitled)
Zinner’s syndrome is a rare embryologic anomaly of the distal portion of the mesonephric duct comprising a triad of ipsilateral renal agenesis, seminal vesicle cyst and ejaculatory duct obstruction. We report ultrasound and magnetic resonance imaging findings of this rare developmental anomaly involving the mesonephric duct, in an asymptomatic 17-year-old boy who would probably remain undiagnosed until later age. The patient presented with no specific symptoms and was incidentally diagnosed on imaging exams.